Two-Site Occupation for Exploring Ultra-Broadband Near-Infrared PhosphorDouble-Perovskite La2MgZrO6:Cr3 - Zeng, Huatao; Zhou, Tianliang; Wang, Le; Xie, Rong-Jun (Chemistry of materials, 2019)
The near-infrared phosphor-converted light-emitting diodes (NIR pc-LEDs) have great potential in food industry and medical fields. For applications based on NIR spectroscopy, the next generation of NIR pc-LEDs is in a high demand of a spectrum with a much broader full width at half-maximum (fwhm), which triggers the discovery of novel broadband NIR phosphors. In this work, the Cr3+-doped La2MgZrO6 (LMZ) was successfully synthesized by a conventional solid-state method in a reducing atmosphere, and the double-perovskite oxide LMZ with two distorted octahedral sites finally led to an ultra-broadband Cr3+ emission centered at 825 nm with an extremely large fwhm of 210 nm and an internal quantum efficiency of ∼58%. The experimental data and theoretical calculation confirmed that two available Cr3+ sites with different crystal field environments contributed to the broadband emission. The crystal field parameters, decay time, and temperature-dependent photoluminescence properties were investigated and discussed to further understand the luminescence of Cr3+ in LMZ:Cr. The suitability of the title NIR phosphor in multifunctional pc-LEDs was demonstrated by pumping it with blue, green, and/or red LED chips.